The akha way [videorecording] - Hainsfurther, Sharon; Flannery, Mary (Watertown, MA. : Documentary Educational Resources, 1999)
Depicts the culture of the Akha, an Asian people, mainly in Southern China, Burma and Northern Thailand. The Akha Way, or Akhazaunh, is the code by which they live and it is their religion, law and philosophy. This film shows the ritual sacrifice of a water buffalo, a shaman healing ceremony, the reading of a pig's liver after a new house is built and other customs. Today the Akha Way is fast disappearing due to outside forces which are eroding the cultural heritage of the the tribes